1991
DOI: 10.4294/jpe1952.39.391
|View full text |Cite
|
Sign up to set email alerts
|

Why Does the Higashi-Izu Monogenetic Volcano Group Exist in the Izu Peninsula?: Relationships between Late Quaternary Volcanism and Tectonics in the Northern Tip of the Izu-Bonin Arc.

Abstract: A synthesis of available geological, petrological, and geophysical data was made to construct a model for explaining the relationships between the late Quaternary volcanism (the Higashi-Izu monogenetic volcano group, HIMVG) and tectonics in and around the Izu Peninsula, Japan. The Izu Peninsula and adjacent areas can be divided into three tectonic blocks: the western Izu (W-Izu), eastern Izu (E-Izu), and Oshima-Zenisu blocks. The vents or intrusions of the HIMVG are formed as open cracks aligning with the near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 37 publications
(42 reference statements)
5
35
0
Order By: Relevance
“…Vent alignment 2 of Hamuro (1978) may reflect the submerged cone sheet as proposed by Miyajima et al (1985). Paleomagnetic directions and stratigraphic relationships of the erupted materials suggest linear arrangements of the vents trending NW-SE, which is consistent with the direction of the maximum compressive stress field around the Izu Peninsula (Koyama and Umino, 1991). This fact indicates that the direction of magmatic intrusion is not controlled by a local stress field around the magma chamber but is determined according to the regional stress field.…”
Section: Sample Descriptionsupporting
confidence: 71%
See 2 more Smart Citations
“…Vent alignment 2 of Hamuro (1978) may reflect the submerged cone sheet as proposed by Miyajima et al (1985). Paleomagnetic directions and stratigraphic relationships of the erupted materials suggest linear arrangements of the vents trending NW-SE, which is consistent with the direction of the maximum compressive stress field around the Izu Peninsula (Koyama and Umino, 1991). This fact indicates that the direction of magmatic intrusion is not controlled by a local stress field around the magma chamber but is determined according to the regional stress field.…”
Section: Sample Descriptionsupporting
confidence: 71%
“…The only historic eruption of 1989 on the seafloor off the coast of Ito has shown that this volcano group is still active. Recent study on this volcano group (Koyama et al, 1990;Koyama and Umino, 1991) has suggested that it has erupted since 100 thousand years B. P., much earlier than it was thought by the previous workers (Aramaki and Hamuro, 1977;Hamuro, 1978). Total volume of erupted materials amounts to 2.5km3, one sixth of which are occupied by lava flows and pyroclastic materials ejected from Omuroyama.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In fact, the exact location and nature of the plate boundaries in this region are the problems under debate (Nakamura and Shimazaki, 1981;Kaizuka, 1984;Ishibashi, 1978Ishibashi, , 1985Ishida, 1990;Yoshida, 1991;Koyama et al, 1991). The situation has been made more complicated by the proposal that central Honshu should be separated in the Fossa Magna region adjacent to the Izu Peninsula by a nascent plate boundary between the Eurasian and North American plates (Kobayashi, 1983;Nakamura, 1983).…”
Section: Fundamental Tectonic Structurementioning
confidence: 99%
“…The east part of the Izu block is a volcanically distinctive area in which Quaternary monogenetic volcanoes are widely distributed (Aramaki and Hamuro, 1977;Hamuro et al, 1983;Koyama et al, 1991). The 1989 volcanic eruption at Teisi Knoll is regarded as one of the activities of the monogenetic volcano group (Soya et al, 1989).…”
Section: Introductionmentioning
confidence: 99%